The Associations between Exclusive Breastfeeding, Complementary Feeding, and the Risk of Stunting in Children Under Five Years of Age: A Path Analysis Evidence from Jombang East Java - Barir, Baroroh; Murti, Bhisma; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2019)
Background: Stunting in children becomes a health problem that gets priority and must be addressed immediately. Delayed development, a decrease in cognitive function and immune function and the risk of diabetes mellitus, coronary heart disease, hypertension, and obesity are the effects of stunting. This study aimed to analyze the determinants of stunting in children aged 2-3 years in Jombang, East Java. Subjects and Method: This was an analytic observational study with case-control design. The study was carried out at Plandaan and Kabuh community health centers, Jombang, East Java, from March to April 2019. A sample of 200 children aged 2-3 years old was selected by fixed disease sampling. The dependent variable was stunting. The independent variables were maternal age, maternal height, maternal attitudes, maternal occupation, birth length, infant birth weight, exclusive breastfeeding, breastfeeding, family income, mother’s education, and mother’s know